Capital Structure and Performance: Examination of Managerial Ability as Moderating Role - Alex Johanes Simamora (Asian Academy of Management Journal of Accounting and Finance, 2021)
The debate on capital structure contribution occurs in many studies of finance. This research aims to examine the moderating role of managerial ability on the effect of capital structure on firms’ performance. The research sample includes 383 manufacturing firms- years listed on the Indonesian Stock Exchange. The capital structure is measured by the leverage variables. Managerial ability is measured by a manager-specific efficiency score. The analysis method uses firm and year fixed effect regression tests. Based on the result, higher debts can improve firms’ performance when higher managerial ability occurs. Managers with managerial ability can promote the debt benefits and mitigate the cost of the debt so that the use of debt can increase firms’ performance. This research provides new evidence that managerial ability can fill the gap of inconsistent previous findings of the relationship between capital structure and performance.